Coping strategies of economically (partially) inactive households: the case of Croatia - Bagić, D; Dobrotić, I; Lažnjak, J; Rodik, P; Vučkovićjuroš, T (De Gruyter, 2017)
How do households with inactive or unemployed members face growing risks and uncertainty? The present study tackles this problem with a case study on Croatia, a country at the bottom of the European Union’s (EU) scale of economic activity rate. The low level of activity that has characterized Croatia for more than twenty years has been accompanied by a continuously high unemployment rate, which has further increased since 2009. In this context, households with (long-term) inactive or unemployed members have had to develop alternative coping strategies. In order to identify and examine these strategies, in 2014 we conducted a mixed-method study, including a quantitative survey of 453 households and 37 semi-structured interviews. We identified six household strategies, more or less ‘successful’ in terms of the household’s material position. In this essay we further examine these strategies’ characteristics and implications, with a focus on the profiles of households employing specific strategies.